A Study on the Ontologies Developed Based on the Principles of Open Biomedical Ontologies Foundry - Nader Alishan Karami; Mohsen Hajizeinalabedini; Iraj Radad; Seyed Javad Ghazi Mirsaeed (Tehran University of Medical Sciences, 2019)
Background and Aim: Ontologies facilitate data integration, exchange, searching and querying. Open Biomedical Ontologies (OBO) Foundry is a solution for creating reference ontologies. In this foundry, the design of ontologies is based on established principles which allow for their interactions as a single system. The purpose of this study is to determine the main features of ontologies developed based on foundry principles. Materials and Methods: This descriptive cross-sectional study (2017) retrieved data about the ontology components, subject, language and tool from the OBO foundry website, and OntoBee (the default linked data server for the foundry ontologies). The frequency of classes, instances, Object Properties, DataType Properties and Annotation Properties are classified by the use of descriptive statistics. Results: The main subjects of 151 ontologies were Anatomy, Health and Phenotype. Most languages and tools were, respectively, OBO and OBO-edit versions used for the development of ontologies. Five percent of ontologies contained more than 78977 classes, 150 object relations, 39 DataType relations, 110 annotation relations, and 356 instances. Conclusion: Increasing the number of ontologies developed based on OBO foundry principles as well as using OBO language and OBO-Edit is indicative of the fact that ontology developers have accepted the principles and tools.